Dmanisi hominin fossils and the problem of the multiple species in the early Homo genus - Guimarães, Santiago Wolnei Ferreira; Merino, Carlos Lorenzo (Nexus (Hamilton), 2015)
The D4500 (Skull 5), dated 1.8 Mya., is the most complete fossil within the set of five skulls found in Dmanisi, Georgia, as well as any other fossils associated to contexts of occupation of the early Pleistocene. Its discovery has brought forward the debate of the plurality of species, not just at the beginning of the Homo genus, but for much of its evolution.  The Skull 5 fossil presents a mixure of primitive and derivates characters associated to the Homo erectus and Homo habilis sensu lato. Based on the data referring to the five skulls researchers have considered the hypothesis of a single evolving lineage of early Homo as a mode to explain the great variation range of the Dmanisi fossils, similar to the range found in habilines. In other words, it is an explanation that reiterates the existence of only one unique species in the early of the Homo genus: the Homo erectus in a sensu lato. Our work consists of evaluating such supposition through the calculation of the coefficient of variation, which was estimated from the referred set and compared to those from already known species. Results achieved did not support the thinking that one unique species was able to bear all fossils of the early of Homo genus.